Philosophical Meta-Story about The Little Prince as a Synergy of Book and Film Industries: On the Possibilities of Film Adaptation of Literature for Children and Youth - Rusňáková, Lenka; Kopecká, Zuzana (Communication Today, 2022)
The present study explores the ways in which children’s and young adult literature is adapted to film, as these stories allow the autonomous world of childhood, distinctly different from the adult perspective, to emerge. At the same time, however, literary testimony presented through children’s perception and interpretation of reality can bring contemporary social or existential problems closer to the adult reader through imagery accessible to people of all ages. A representative result of the confrontation of the children’s and the adult world is also the literary work of the French writer Antoine de Saint-Exupéry, originally intended for children. The depth and topicality of the philosophical fairy tale The Little Prince (originally in French, Le Petit Prince, first published in 1943) lie in the fact that it is one of the world’s most translated fairy tales, which has been the basis for numerous dramatic adaptations, re-editions and film adaptations. The main aim of the study is, therefore, to clarify the way the philosophical metanarrative of The Little Prince is expressed in the literary source and in the audiovisual film of the same name, The Little Prince (Le Petit Prince, 2015, directed by Mark Osborne). In order to achieve this goal, we apply a narrative analysis of both research materials based on analytical categories defined in the methodological section of the study. The identification and subsequent comparison of the chosen analytical categories is the starting point for determining the mode of filmic adaptation of the literary subject matter. The categorisation of film adaptations of literary works according to L. Giannetti and T. Leitch becomes the focus. Within the theoretical delineation of the issue under discussion, we point to its interdisciplinary character (the ‘intermingling’ of media and communication studies, literary criticism, but also media philosophy, film studies and other related disciplines), emphasising the cultural overlap of the philosophical metatheory of The Little Prince. This timelessness opens up space for further research into the possibilities of the story’s cinematic adaptations and interpretative planes. Characteristic logical-conceptual procedures are employed to achieve the stated aims.